Misia z Godebskich - Kossak, Ewa K. (Warszawa : Wydawn. ALFA, 1994)
A biography of a Polish woman of fascinating character who lived in Paris in the first half of the 20th century and who met the literary figures of the time.
Includes bibliographical references (p. 477-[483]) and index.
Keywords: Sert, Misia, -- 1872-1950.; Polish people -- France -- Paris -- Biography; Arts -- France -- Paris -- Biography; Paris (France) -- Biography